2018
DOI: 10.1007/s11033-018-4309-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Warburg effect and stemness in CD133+ve cancer stem cells from Saos-2 (osteosarcoma) cell line under hypoxia

Abstract: Cancer stem cells (CSCs) which are known to be residing deep inside the core of the tumor in its hypoxia niche is responsible for relapse of cancers. Owing to this hypoxic niche, the residing CSCs simultaneously fuel their stemness, cancerous and drug resistance properties. Attributes of CSCs are still not properly understood in its hypoxia niche. Addressing this, we sorted CSCs from Saos-2 (osteosarcoma) cell line using CD133 antibody. The CD133 CSCs exhibited quiescent cell proliferation in DNA doubling, Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The authors showed that this re-growth was associated with the presence of cancer stem cells (CSCs) in the lung tumor cell population [ 52 ]. In the present study, we did not investigate the presence of CSCs within the sub-populations of SAOS and HT29 cells selected after γ-ray irradiation, although their appearance and enrichment after drug treatments is a possible event, as reported by others [ 53 , 54 ]. For these reasons, we cannot exclude that “senescence associated-stemness” can be responsible for IR resistance in SAOS400 and HT500 cell lines.…”
Section: Discussionmentioning
confidence: 89%
“…The authors showed that this re-growth was associated with the presence of cancer stem cells (CSCs) in the lung tumor cell population [ 52 ]. In the present study, we did not investigate the presence of CSCs within the sub-populations of SAOS and HT29 cells selected after γ-ray irradiation, although their appearance and enrichment after drug treatments is a possible event, as reported by others [ 53 , 54 ]. For these reasons, we cannot exclude that “senescence associated-stemness” can be responsible for IR resistance in SAOS400 and HT500 cell lines.…”
Section: Discussionmentioning
confidence: 89%
“…Effect of AXN (dose dependent) on cell viability was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide dye reduction was performed according to our pervious procedure [ 14 ]. Finally, the concentrations of AXN resulting in 50% reduction in cell viability at 24h (i.e., 50µM/ml) were then calculated and were used for further experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the phosphoinositide 3-kinase (PI3K)/Akt pathway becomes activated under hypoxic conditions, resulting in changes in the activities of various enzymatic biological pathways, including glucose metabolism (Xie et al, 2019). HIF1A has been demonstrated to be a glycolysis promoter that is regulated by PI3K/Akt pathway, and increased HIF1A expression induces the transcription of PDK4 (Kaelin and Ratcliffe, 2008;Lambert et al, 2010;Idelevich et al, 2011). PDK4 can phosphorylate the pyruvate dehydrogenase complex, inhibiting the oxidative decarboxylation of pyruvate into acetyl-CoA.…”
Section: Glycolysis Is Upregulated In Gannan Yaks During Hypoxiamentioning
confidence: 99%